EFESIENSI MUSICOOL-22 DENGAN PROSES RETROFIT PADA AC MEREK DAIKIN 3 PK DI UNIT REKTORAT UNIMUS - Khoeri -; Achmad Solichan; Samsudi Raharjo (MEDIA ELEKTRIKA, 2017)
Mechanical air conditioning to regulate the temperature , circulation , humidity and cleanliness of the air inside the room . Air conditioning (Air Conditioner) maintaining the condition of the air inside so that the occupants of the room to be comfortable . The purpose of this study was to compare the efficiency of the use of refrigerant R - 410A and MC - 22 at the brand split air conditioners Daikin 2 PK with retrofit methods . The results obtained during the test indicates the use of refrigerants MUSIcool-22 more efficient 19.51 % compared with the use of refrigerant R - 410 Aand Performance temperatures MUSIcool-22  colder  0,50C of Performance temperature refrigerant R - 410A. Keywords: Air Conditioning, R-410A, MUSIcool-22, Retrofit, Temperature